EXTRASYSTOLE: ELECTROPHYSIOLOGICAL MECHANISMS, CAUSES, CLINICAL SIGNIFICANCE - G.T. Mamedova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Extrasyistols (ES) are premature ectopic heart cuts. The pathological impulse leading to the extrasystole occurs at various levels.Atrial and atrial and ventricular extrasystoles are sometimes united under the name "Extrasyistols "due to their similar clinical value.